Alternative strategies to platelet transfusion. (29th January 2016) - Lozano, M.; Cid, J.
Abstract : Although platelet transfusions continue to be the mainstay in the management of patients suffering from qualitative and quantitative disorders, several strategies might be considered when trying to reduce or avoid platelet transfusions. Those include assuring a higher haemoglobin level and pharmacological interventions. Several studies in vitro and in vivo suggest that higher haematocrit decreases bleeding time in anaemic patients. This effect might be due to the haemorheological effect of red blood cells that expel platelets towards the wall optimizing the interaction of circulating platelets with the injured subendothelium. Several drugs have shown the capacity for improving the haemostasis and decreasing the bleeding diathesis in patients suffering from thrombocytopathies and/or thrombocytopenias, although the evidence is scarce and sometimes contradictory. Among antifibrinolytic drugs, two synthetic derivates are available, epsilon aminocaproic acid and tranexamic acid, although the latter one is the preferred for most of indications, given its higher and more sustained antifibrinolytic activity in tissues and lower and less frequent dosing. A few reports have shown the efficacy of desmopressin in treating patients with quantitative platelet disorders and Bernard–Soulier syndrome. Patients with Glanzmann thrombasthenia do not respond to desmopressin. Recombinant activated factor VII is currently approved in the European Union for treating patients with Glanzmann thrombasthenia refractory to platelet transfusions due to antibodies to GPIIb‐IIIa and/or HLA. Currently, we have available two thrombopoietin analogues (romiplostim and eltrombopag) that have been used in patients with quantitative and/or qualitative platelet disorders. Several platelet substitutes are currently under development and one is being tested in healthy volunteers, but none is available yet in the market.